The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/j.1469-7793.1999.0895p.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the pathways mediating ipsilateral and contralateral motor‐evoked potentials in human hand and arm muscles

Abstract: Growing evidence points toward involvement of the human motor cortex in the control of the ipsilateral hand. We used focal transcranial magnetic stimulation (TMS) to examine the pathways of these ipsilateral motor effects. Ipsilateral motor‐evoked potentials (MEPs) were obtained in hand and arm muscles of all 10 healthy adult subjects tested. They occurred in the finger and wrist extensors and the biceps, but no response or inhibitory responses were observed in the opponens pollicis, finger and wrist flexors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
289
7
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(333 citation statements)
references
References 47 publications
23
289
7
3
Order By: Relevance
“…Ipsilateral responses had a longer latency than contralateral responses of around 4 msecs. These findings are in agreement with those of Ziemann et al (1999) who demonstrated slower ipsilateral responses in upper limb muscles obtained more prominently from sites lateral to the optimal stimulation site for contralateral responses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ipsilateral responses had a longer latency than contralateral responses of around 4 msecs. These findings are in agreement with those of Ziemann et al (1999) who demonstrated slower ipsilateral responses in upper limb muscles obtained more prominently from sites lateral to the optimal stimulation site for contralateral responses.…”
Section: Discussionsupporting
confidence: 92%
“…As with the findings of Ferbert et al (1992) in the erector spinae and Ziemann et al (1999) in hand and arm muscles, ipsilateral responses were evoked when stimulating at lateral sites. The midline ipsilateral responses seen using the original mapping protocol may be the result of unintentional stimulation of the opposite cortex since they disappear when mapping using a sagittal coil orientation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The inhibitory influences of M1 on the activation of the ipsilateral hand, however, may to a significant extent be relayed (i.e., timed) below the cortex. This relay probably includes multiple (active) levels along 107 the neuroaxis-like ipsilateral oligosynaptic pathways and corticoreticulo-or corticopropriospinal projections (Ziemann et al 1999;Leocani et al 2000). Irrespective of the exact location of the postulated inhibitory mechanisms, the proposed model indicates that an eventual loss of inhibition may result in instabilities and phase transitions or, more generally, unintended motor output (Armatas et al 1994;Leinsinger et al 1997;Daffertshofer et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Ipsilateral MEPs can be elicited in selected arm muscles in non-impaired adults when TMS is applied at high intensity and there is background activation of the target muscle (Carr et al 1994;Colebatch et al 1990;MacKinnon et al 2004;Ziemann et al 1999). Ipsilateral MEPs are more easily elicited in proximal than distal muscles, however, even when present, the contralateral projections are much stronger (Bawa et al 2004).…”
Section: Ipsilateral Mep Prevalencementioning
confidence: 99%